2022
DOI: 10.29244/jpsl.12.2.363-371
|View full text |Cite
|
Sign up to set email alerts
|

Gaining Aquaculture Blue Growth with Low Carbon Emission Shrimp Farming Technology

Abstract: Carbon emissions and their relation to shrimp farming activities getting more attention by researchers and environmentalists. Emissions of carbon and other greenhouse gases are concluded as drivers of climate change due to global warming. On the contrary, climate change is proven to determine the continuity and sustainability of shrimp farming activities. The dynamics of carbon and profitability are different for the three cultivation technologies (extensive, semi-intensive, and intensive), it caused by differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The main principle of blue carbon management is to reduce and minimize emissions and increase the carbon sink. Rationalization of shrimp farming area on the coast of Karawang Regency can reduce carbon emissions and increase the ability to absorb CO2 and carbon stocks Rifqi et al (2022). This study suggested that the existence of mangrove protected areas in a spatial pattern will provide environmental services, including absorbing and storing carbon, filtering and absorbing organic matter from pond effluent, and also will increase the carrying capacity of the environment to support the continuity and sustainability of shrimp farming activities in the area.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…The main principle of blue carbon management is to reduce and minimize emissions and increase the carbon sink. Rationalization of shrimp farming area on the coast of Karawang Regency can reduce carbon emissions and increase the ability to absorb CO2 and carbon stocks Rifqi et al (2022). This study suggested that the existence of mangrove protected areas in a spatial pattern will provide environmental services, including absorbing and storing carbon, filtering and absorbing organic matter from pond effluent, and also will increase the carrying capacity of the environment to support the continuity and sustainability of shrimp farming activities in the area.…”
Section: Resultsmentioning
confidence: 90%
“…The amount of emission per kg of shrimp produced will probably certainly be much lower on land that does not convert mangroves and have better land productivity, such as in semi-intensive and intensive ponds. However, there are still limited studies that explain the potential for carbon uptake and Rifqi et al 2022 storage during the shrimp farming process in aquaculture. Furthermore, there is a potential for carbon absorption by phytoplankton and carbon stocks in the form of phytoplankton and shrimp/fish biomass (Widigdo et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations